The use of Malaysian ilmenite as weighting material in drilling mud - Idris, Ahmad Kamal; Ismail, Issham; Othman, Ariff; Ha, Kwong Tak (USM, 1994)
This paper discusses the prospect of utilising Malaysia ilmenite as weighting material in drilling mud. The discussion was based on laboratory experiments. The performance of local ilmenite was compared to barite in a lignosulphonate mud system. The results showed that for a given mud density, ilmenite gave a lower solid content. Compared with barite, ilmenite gave a much higher yield point and gel strength, but there were little differences in apparent viscosity and plastic viscosity. Ilmenite was also found to give a higher API fluid loss than barite. In contrast, the fluid loss produced by ilmenite sample via the HPHT filter press was found to be much lower compared to the barite sample. The higher yield point and gel strength of the mud which utilised local ilmenite as weighting material could be lowered by increasing the concentration of lignosulphonate in the mud. There was no indication of incompatibility of lignosulphonate in the mud system. Based on this preliminary study, it was concluded that the local ilmenite has the potential to be used as weighting material in drilling mud.